Becoming a mentor: The impact of training and the experience of mentoring university students on the autism spectrum - Hamilton, J.; Stevens, G.; Girdler, Sonya (Public Library of Science, 2016)
While it is widely recognised that the number of young adults diagnosed with Autism Spectrum Disoders (ASD) is increasing, there is currently limited understanding of effective support for the transition to adulthood. One approach gaining increasing attention in the university sector is specialised peer mentoring. The aim of this inductive study was to understand the impact of peer mentor training on seven student mentors working with university students with an ASD. Kirkpatrick’s model framed a mixed methods evaluation of the mentors’ training and description of their experience. Overall, the training was well received by the mentors, who reported on average a 29% increase in their ASD knowledge following the training. Results from the semi-structured interviews conducted three months after the training, found that mentors felt that the general ASD knowledge they gained as part of their training had been essential to their role. The mentors described how their overall experience had been positive and reported that the training and support provided to them was pivotal to their ability to succeed in as peer mentors to students with ASD. This study provides feedback in support of specialist peer-mentoring programs for university students and can inform recommendations for future programs and research.